Ion-exchange medium coated with abundant small zwitterions for the purification of soluble proteins. Issue 4 (1st April 2021) - Chen, Tong; Yang, Linyu; Yang, Xiaolan; Liao, Fei
Abstract: A new ion-exchange medium was prepared from magnetic particles of ∼1.0 µm through coating with small zwitterions and then functionalizing with ampholytic groups for the isoelectric point of ∼6.4 and denoted MSP-ZEWB. With Meyerozyma guilliermondii uricase (MGU) as the model of soluble proteins, the purification of a protein via ion-exchange was compared between MSP-ZEWB through elution in discontinuous mode and Toyopearl SP-650C as a classical ion-exchange medium through elution in continuous mode. MGU was adsorbed at pH 7.6 or 8.0 and eluted via competitive displacement by NaCl or electrostatic repulsions with an elution buffer at pH 10 to reverse the type of net charges of MGU. From MSP-ZEWB, MGU was eluted more rapidly with the elution percentages higher than those from Toyopearl SP-650C. For yielding a unit of MGU activity, MSP-ZEWB gave the elution solution volumes that were ∼50% of those obtained with Toyopearl SP-650C. The yields of MGU of the highest purity from MSP-ZEWB were higher than those from Toyopearl SP-650C, but the highest purification folds with both media were comparable. MSP-ZEWB regenerated for 16 times still showed the consistent purification efficacy. Therefore, the ion-exchange media bearing small zwitterion coats showed great promise for the purification of soluble proteins.